Technical assistance to strengthen national agricultural research organizations’ capacity to use digital sequence information. A submission from CGIAR - López Noriega, Isabel; Rouard, Mathieu; Halewood, Michael; Sackville-Hamilton, N. Ruaraidh; Bhattacharjee, Ranjana; Carvajal Yepes, Monica; Domelevo Entfellner, Jean-Baka; Hearne, Sarah Jane; Hendre, Prasad; Kehel, Zakaria; Kreuze, Jan F.; Kuldeep, Singh; et al. (2023)
CGIAR submitted this report in response to an open request from the Plant Treaty Secretary, for submissions regarding, a) contracting parties’ and stakeholders’ capacity building needs for accessing and using digital sequence information (DSI)/genomic sequence data (GSD) and b) ‘technical assistance’ and ‘actions taken’ by stakeholders (including CGIAR) ‘to reduce the existing gap on capacity regarding DSI/GSD’. The primary objective of this paper is to respond to the second part of the request by sharing information about how CGIAR Centers and Initiatives have been assisting organizations outside CGIAR to access, generate, share, analyse, and use DSI for the conservation of plant genetic resources for food and agriculture (PRGFA) and for the use of PGRFA in pre-breeding and breeding. This paper does not provide an exhaustive account of all of the Centers’ relevant activities, but it does provide a general overview of the kinds of activities in which the Centers have been engaged. CGIAR very much appreciates the Governing Body’s initiative, as expressed in Resolution 16/2022, to ask the Plant Treaty Secretariat to gather and synthesize information about both demand for, and supply of, capacity strengthening related to DSI linked to plant genetic resources for food and agriculture, with the overall objective of working to close the capacity gap between developed and developing countries. It is our hope that, based on the outcomes of this exercise, CGIAR will be able to further adapt and improve its own approach to capacity sharing in response to needs prioritized by the Governing Body.